Effect of Mismatch Repair Status on Outcome of Early-Stage Grade 1 to 2 Endometrial Cancer Treated With Vaginal Brachytherapy. (January 2022) - Russo, Andrea L.; Lee, Larissa J.; Wo, Jennifer Y.; Niemierko, Andrzej; Park, Diane; Alban, Gabriela; King, Martin; Philp, Lauren; Growdon, Whitfield B.; Oliva, Esther; Spriggs, David R.; Yeku, Oladapo O.
Abstract : Objectives: The objective of this study was to determine if deficiency of mismatch repair (dMMR) proteins in patients with early-stage favorable endometrial cancer treated with vaginal brachytherapy (VB) is associated with increased recurrence. Materials and Methods: A multi-institutional retrospective cohort study of 141 patients with stage I to II grade 1 and 2 endometrioid adenocarcinoma treated with surgery and adjuvant VB was performed to compare recurrence risk in dMMR (n=41) versus MMR-preserved (pMMR) (n=100). Additional clinical and pathologic risk factors were also collected. Univariate analysis and multivariable analysis Cox regression analysis was performed to identify factors associated with any recurrence. Kaplan-Meier method and log rank test were used to compare recurrence free survival and overall survival (OS). Results: Median follow up was 42 months. Forty-one patients (29%) were dMMR. There were 7 recurrences (17%) in dMMR versus 4 recurrences (4%) in pMMR ( P =0.009). On univariate analysis of any recurrence, both dMMR (hazard ratio: 5.3, P =0.008) and stage (hazard ratio: 3.8, P =0.05) were statistically significantly associated with time to first recurrence. The 5-year recurrence free survival was 90% (95% CI: 73%-96%) in pMMR versus 61.0% (95% CI: 19%-86%) in dMMR ( P =0.003). Five-year OS was 96% (95% CI: 76%-99%) in pMMR versus 86% (95% CI: 62%-95%) in dMMR ( P =0.03). Conclusions: MMR deficiency in stage I to II grade 1 to 2 endometrial cancer patients treated with adjuvant VB alone was associated with statistically significant increased risk for any recurrence and worse OS. MMR status may be an important prognosticator in this cohort of patients warranting adjuvant treatment intensification in the clinical trial setting.